STRENGTHENING STUDENTS' LEARNING MOTIVATION AT MADRASAH IBTIDAIYAH THROUGH THE INTEGRATION OF TRADITIONAL GAMES AND DIGITAL LEARNING MEDIA IN THEMATIC LEARNING - Nimas Naila Maratus Sholehah; Muhammad Kholil (PT. Radja Intercontinental Publishing, 2026)
Learning motivation is a fundamental factor that influences student engagement in the learning process, especially at the Madrasah Ibtidaiyah level . In practice, thematic learning in the classroom still often shows a low level of student participation due to the use of monotonous methods and lack of providing meaningful learning experiences. This study aims to analyze how the integration of traditional games and digital learning media can strengthen student learning motivation in thematic learning in Madrasah Ibtidaiyah , with the research context at MI Darullughah Wal Karomah (MI DWK), Indonesia. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Observations were conducted to observe learning activities and student engagement in the classroom, while interviews were conducted with teachers and students to gain an in-depth understanding of the learning experience. Data analysis was carried out through the stages of data reduction, data presentation, and interpretation of research findings. The results of the study indicate that the integration of traditional games and digital learning media in MI DWK is able to create a more interactive and participatory learning atmosphere . Students showed increased engagement through discussion activities, group work, and participation in games integrated in thematic learning. Digital media also strengthens students' conceptual understanding through more visual and engaging presentation of material, thus contributing to increased learning motivation.